(untitled) (Research, Society and Development, 2023)
This research aims to discuss the use of Pre-Exposure Prophylaxis (Prep). Included is information about HIV that elucidates epidemiological data of the disease and the importance of the content to be discussed. The target group for this therapy is described, as well as the action mechanism of the different components of Prep (emtricitabine and tenofovir disoproxil fumarate). Other points addressed are the analysis of liver and kidney function after the use of the medicine as well as the management and maintenance of its use together with the approach of other contraceptive methods. To cover these objectives, articles and journal publications were collected in different databases with information on epidemiological data, dosage, etc. It is hoped that the review will be able to compile the data listed in the objectives and disseminate new and solid information about this prevention method, still poorly disseminated.